Clinical case of basal cell carcinoma therapy using 5 % imiquimod cream - H. I. Makurina; O. I. Мakarchuk; I. P. Dmytrenko; A. V. Holovkin; L. O. Cherneda (Patologìâ)
Aim. To describe clinical case of the basal cell carcinoma treatment, determine personalized diagnostic algorithm of the patient management with further selection of the therapy method regarding visual, dermatoscopic and pathomorphological picture of disease.